Information Needs and Information Seeking Behavior of Farmers in a Local Community in Odisha:An Analytical Study - Mahapatra, Rabindra K. (Journal of Information and Knowledge, 2016)
Every effort has been taken by Government authorities to empower the farming community with information. Farmers have taken interest to know the modern techniques of farming to improve agricultural productivity. Farmers must have latest information and technological know-how on modern agriculture. In this situation determining information needs and identifying their information seeking behavior is an imminent task for the information intermediary. Hence this study undertaken in four villages in Odisha is an attempt in this direction which is designed to reflect the current knowledge of the farmers on agriculture, their information needs, seeking behavior, communication channels, the priority of information, and ways and means of better information related situation, etc.